Effect of Column Diameter on the Performance of an Ion Exchange System in Reducing Water Hardness - Widya Yeni Rawati; Sunardi; Sri Widarti; Sumarja; Muhammad Nur Alim (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2025)
Ion exchange is an effective method for removing hardness ions such as Ca2+ and Mg2+ from water, and its performance is strongly influenced by column design parameters. This study aims to evaluate the effect of column diameter on the efficiency of a sequentially operated cation–anion ion exchange system at a constant flow rate of 10 L/h. Six column diameters (20, 25, 30, 35, 40, and 50 mm) were tested using synthetic solutions. The results showed that the 30 mm column achieved the highest ion-exchange performance, with a removal efficiency of 92.47%. This column also produced the most well-defined breakthrough curve, yielding an exchange capacity of 8.76 mg/g, equivalent to 0.437 meq/g for Ca2+ and 0.720 meq/g for Mg2+. These findings indicate that the 30 mm diameter provides an optimal balance between contact time and flow distribution, resulting in superior ion exchange efficiency.